Exploring the impact of climate change on tour guides' practices in the Arctic - Karjalainen, Katja (fi=Lapin yliopisto|en=University of Lapland|, 2023)
Climate change is the greatest threat for humankind and life as we know it. It is inevitably bringing new practices to our daily lives. The climate is warming four times faster in the Arctic region than elsewhere on the globe, having already caused changes in everyday life and practices. Tourism is one of the biggest livelihoods in Finnish Lapland, so the influence of climate change cannot be ignored when talking about the future of tourism business in the Arctic. Covid-19 revealed the vulnerability of the tourism field, but now, when influence of climate change is already well studied and its effects are known, businesses can prepare for these changes and mitigate them through their own actions. Climate change is bringing new challenges to tourism in Lapland, for example increasing cloudiness will complicate the Northern Lights tours and the changing temperatures bring challenges for operating tours. This thesis explores how the guides at a small tour operator are changing their working practices in response to climate change and how the guides are experiencing these changes. Another issue is how the guides feel about the future and what hopes they have for tourism with the facts of climate change. Qualitative research was used to gather the data and it consists of five semi-structured interviews and participating observation. The findings indicate that new practices regarding communication, safety issues and implementing tours have emerged. The findings also reveal concerns that the guides were experiencing regarding the future and suggest new practices that tour companies can adopt. The results also reveal some ethical dilemmas that the tour guides are facing while working in the tourism industry, as it accelerates climate change.